Quantitative trait loci analysis of blast resistance in Oryza sativa L. 'Hokuriku 193' - Nagaoka, Ichiro (Breeding science, 2017)
To investigate the genetic background responsible for blast resistance in Oryza sativa L. 'Hokuriku 193', QTL analysis was conducted using the F3 lines from the cross [ms-bo] Nekken 2 × Hokuriku 193 that were artificially infected with rice blast fungus (Magnaporthe grisea). QTLs were detected on chromosomes 1, 4, 6 and 12 that correlated with greater blast resistance in the Hokuriku 193-type lines. Notably, the QTL on chromosome 12 had a major effect and localized to the same region where Pi20(t), a broad-spectrum blast resistance gene, is positioned, suggesting strongly that the blast resistance of Hokuriku 193 was controlled by Pi20(t). Also, QTL analysis of the lines found to have no Pi20(t) detected two QTLs on chromosome 4 (qBR4-1 and qBR4-2) and one QTL on chromosome 6 (qBR6), of which qBR4-2 and qBR6 correlated with higher percentages of resistant plants in the Hokuriku 193-type lines. The blast susceptibility of BR_NIL (a NIL of Hokuriku 193 from which Pi20(t) was eliminated) was greater than that of Hokuriku 193, suggesting that elimination of Pi20(t) may markedly increase blast susceptibility. The disease severity of BR_NIL was mild, which might be the effect of qBR4-2 and/or qBR6